Functional properties of the Drosophila melanogaster inositol 1,4,5-trisphosphate receptor mutants. - Srikanth, S.; Wang, Z.; Tu, H.; Nair, S.; Mathew, M.K.; Hasan, G.; Bezprozvanny, I. (Biophysical Journal, 2004)
The inositol (1,4,5)-trisphosphate receptor (InsP(3)R) is an intracellular calcium (Ca(2+)) release channel that plays a crucial role in cell signaling. In Drosophila melanogaster a single InsP(3)R gene (itpr) encodes a protein (DmInsP(3)R) that is approximately 60% conserved with mammalian InsP(3)Rs. A number of itpr mutant alleles have been identified in genetic screens and studied for their effect on development and physiology. However, the functional properties of wild-type or mutant DmInsP(3)Rs have never been described. Here we use the planar lipid bilayer reconstitution technique to describe single-channel properties of embryonic and adult head DmInsP(3)R splice variants. The three mutants chosen in this study reside in each of the three structural domains of the DmInsP(3)R-the amino-terminal ligand binding domain (ug3), the middle-coupling domain (wc703), and the channel-forming region (ka901). We discovered that 1), the major functional properties of DmInsP(3)R (conductance, gating, and sensitivity to InsP(3) and Ca(2+)) are remarkably conserved with the mammalian InsP(3)R1; 2), single-channel conductance of the adult head DmInsP(3)R isoform is 89 pS and the embryonic DmInsP(3)R isoform is 70 pS; 3), ug3 mutation affects sensitivity of the DmInsP(3)Rs to activation by InsP(3), but not their InsP(3)-binding properties; 4), wc703 channels have increased sensitivity to modulation by Ca(2+); and 5), homomeric ka901 channels are not functional. We correlated the results obtained in planar lipid bilayer experiments with measurements of InsP(3)-induced Ca(2+) fluxes in microsomes isolated from wild-type and heterozygous itpr mutants. Our study validates the use of D. melanogaster as an appropriate model for InsP(3)R structure-function studies and provides novel insights into the fundamental mechanisms of the InsP(3)R function.